Analisa Gangguan Failure To Ignite Pada GTG 1.3 Tambak Lorok Dengan Metode RCFA - Roswati Nurhasanah; Gita Puspa Artiani; Gaguk Sujadmiko (JURNAL POWERPLANT, 2014)
PLTGU designed for continuous running, but because of the condition of the network then UP Semarang is conditioned only operate during peak hours or when required by the Dispatcher because other units are holding maintenance or because of something that can not operate. This condition makes the gas turbine units at UP.Semarang often operate with a pattern start / stop, so that the equipment plays an important role in the process of start / stop required for work excellence. The method used to analyze the root cause failure disorders to Ignite Gas Turbine is the method of Root Cause Failure Analysis (RCFA). Based on the results of analysis by method RCFA, disruptions caused by failure to Ignite Liquid Fuel Nozzle Check Valve Failure to obtain Task that is in addition to the regular maintenance schedule after GTG operated by MFO also implement new PM replacement check valve for no.1 to 14 every 6 months , manufacture PM Visual check every 1 week and the addition of a new Prime Minister for a replacement check valve No. 4,5,10,11,13 and 14 every 3 months because often damaged.